ENGLISH TEACHERS’ PERCEPTION ON THE 2013 CURRICULUM AT SMA NEGERI 1 MANOKWARI - Marisa, La Ode; Renyaan, Novalinda (Universitas Papua Manokwari, 2016)
The purpose of this study is to figure out English teachers’ perception on the 2013 curriculum at SMA Negeri 1 Manokwari by looking at their understanding on the concept of the 2013 curriculum, scientific approach, and their views on the assessment of students’ progress. The data was collected through interview and then was analyzed by using “grounded data analysis” method. This qualitative data analysis was chosen in attempting to categorize data thematically and free of any biases. The finding reveals that mostly English teachers agree that the 2013 curriculum is designed to improve students’ competence and it facilitates students to learn actively. Moreover, scientific approaches are defined into three different perspectives. Those are teachers as mediator, learning model, and practical engagement. They also recognize that assessing students’ progress demands them to measure students into three different competences. Theoretically, most of English teachers have understood the notion of the 2013 curriculum. However, several constrains emerge in the implementation of the curriculum. Some common problems are students have various abilities and the lack of supporting learning. Moreover, such concept of the assessment of students’ progress is also still hard to put into practice. For some reasons, there have been some unresolved problems that influence teachers’ performance significantly such as too much aspects of attitude, large size class, and limited number of time spent to learn English in class.